2011
DOI: 10.1111/j.1755-5949.2011.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptors: Their Roles in Disorders of the Central Nervous System and Potential as Therapeutic Targets

Abstract: SUMMARYPhylogenetically, acetylcholine is an ancient neurochemical. Therefore, it is not surprising that cholinergic neurons project extensively throughout the central nervous system, innervating a wide range of structures within the brain. In fact, acetylcholine is involved in processes that underpin some of our most basic central functions. Both muscarinic and nicotinic receptor families, which mediate cholinergic transmission, have been implicated in the pathophysiology of psychiatric and neurological disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 121 publications
(175 reference statements)
2
72
0
6
Order By: Relevance
“…With increasing effort being directed towards developing new drugs to treat the cognitive symptoms of schizophrenia, it would be reasonable to suggest recommencing research on a drug that has already shown therapeutic efficacy. Scarr (2012Scarr ( , 2013, Wess et al (2003), Wezenberg et al (2005). …”
Section: Discussionmentioning
confidence: 97%
“…With increasing effort being directed towards developing new drugs to treat the cognitive symptoms of schizophrenia, it would be reasonable to suggest recommencing research on a drug that has already shown therapeutic efficacy. Scarr (2012Scarr ( , 2013, Wess et al (2003), Wezenberg et al (2005). …”
Section: Discussionmentioning
confidence: 97%
“…The cholinergic M2 receptor gene belongs to a family of muscarinic acetylcholine G-protein coupled receptors with five known subtypes (M1–M5). The M2 receptors in the mesolimbic dopaminergic system play a significant role in modulating the level of dopamine release (Picciotto et al, 2012; Scarr, 2012; Cachope et al, 2012; Oldenburg and Ding, 2011; Witten et al, 2010). This has a important effect in governing the reward system (Mark et al, 2011; Shabani et al, 2010), including modulating the effects of alcohol on it (Adermark et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The cholinergic system in the brain is comprised primarily of nicotinic acetylcholine receptors (nAChRs; Paterson and Nordberg, 2000; Kalamida et al, 2007) and muscarinic acetylcholine receptors (mAChRs; Scarr, 2012; Thiele, 2013), members of the cys-loop superfamily of ligand gated ion channels and G protein-coupled receptors, respectively. Dysregulation of both mAChRs and nAChRs have been strongly associated with several neurological disorders (Janowsky et al, 1972; Freedman et al, 1995; Warpman and Nordberg, 1995; Breese et al, 2000; Salamone and Zhou, 2000; Perry et al, 2001; Woodruff-Pak and Gould, 2002; Ray et al, 2005; Quik et al, 2007; Scarr, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of both mAChRs and nAChRs have been strongly associated with several neurological disorders (Janowsky et al, 1972; Freedman et al, 1995; Warpman and Nordberg, 1995; Breese et al, 2000; Salamone and Zhou, 2000; Perry et al, 2001; Woodruff-Pak and Gould, 2002; Ray et al, 2005; Quik et al, 2007; Scarr, 2012). …”
Section: Introductionmentioning
confidence: 99%